Pendampingan Kunjungan Budaya Wisatawan Prancis Di Kampung Seni Dan Budaya Jelekong Bale Endah Kabupaten Bandung - Rijati, Sri; Intan, Tania; Tri H, Vincentia; Hasanah, Ferli (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
This independent community service activity is entitled the assistance of french travelers visits culture in theVillage of Arts and Culture Jelekong Bale Endah - Bandung. The head of the PPM and members of PPM were acted asFrench interpreter at various activities in the village of GiriHarja or better known as Village of Jelekong. The mainobjective of this activity is to introduce of Arts and culture village of Jelekong as potential tourism assets to Frenchtourists. With this activity, Jelekong is expected  as a center of art and culture which can not only preserve Sundaneseculture but can also be more widely known and be able to develop a variety of artistic and cultural potential that alreadyexists. The activities that have been done are Sundanese culinary cooking demonstrations, painting workshop, Jaipongworkshop, and martial arts workshop. These activities are considered successful because of Jelekong people and Frenchtourist?s participation were high enough in series of activities